A possible teleology of cultural sector data in England. Issue 2 (27th May 2019) - Selwood, Sara
ABSTRACT: In March 2019, Arts Council England (ACE), an official statistics producer, started collecting a new set of data from its National Portfolio Organisations intended to reveal whether those organizations' intentions correlate with the perceptions of their peers and audiences. In a world dominated by quantitative data, the Impact and Insight Toolkit addresses a perceived lacuna and marks a substantial investment in qualitative metrics. ACE also expects it to address a number of other concerns – help organizations self-evaluate, measure their short-term outcomes and advocate more effectively. Indeed, it envisages that an aggregation of the data collected will support the case for sustained public support of the sector. The Toolkit's launch comes at a time when changes to the UK's official statistics are encouraged, and policymakers are looking elsewhere to inform their thinking. The campaigning aspect of ACE's aspirations suggests a model of data collection and analysis distinct from that of official statistics production, valued for its impartiality. This article considers what might happen if the Toolkit, which relates to ACE's role as a development agency, encourages data to be collected and analysed in order to deliver specific outcomes. It reflects on three visions of cultural sector data from the past 50 years: Toffler's The Art of Measuring the Arts, DCMS's Taking Part and ACE's Impact and Insight Toolkit . These suggest a trajectory of cultural sector data determined by increasing importance being attached to institutional interests, and implies that the future of cultural sector data in England may be determined by how ACE addresses its potentially conflicting interests as an official data provider and development agency. Greater investment in the former would more accurately reveal the arts' contribution to economic and social development; greater investment in the latter would encourage the teleological development of cultural sector data designed for sectorial advocacy.